Exploring the Anomala fuscosignata-complex: discovery of two new species from southern China (Coleoptera: Scarabaeidae: Rutelinae) - Zhao, Ming-Zhi; Zorn, Carsten; Liu, Wei-Xin (Zootaxa, 2024)
An investigation towards taxonomy of the Anomala fuscosignata-complex from southern China and northern Vietnam was conducted through direct morphological comparison and molecular phylogenetic analysis, which results in discovery of two new species: A. nanlingensis Zhao, Zorn & Liu, sp. nov. and A. zhengyucheni Zhao, Zorn & Liu, sp. nov. The morphological differences in female genitalia and low genetic divergence as well as their taxonomic implications within Anomalini are discussed.